Пошаговое объяснение:
а) -6(х+2)=4х-17
-6х-12=4х-17
-6х-4х=-17+12
-10х=-5
-х=-5/10
-х=-0,5
х=0,5
ответ 0,5
б) (18-19)-(4-7х)=-73
-1-(4-7х)=-73
-4+7х=-73+1
-4+7х=-72
7х=-72+4
7х=-68
х=-68/7(дробь)
х=-9(целых) 5/7(дробь)
ответ -9 5/7
в) 10х+3(7-2х)=13+2х
10х+21-6х=13+2х
10х-6х-2х=13-21
2х=-8
х=-8/2
х=-4
ответ -4
г) -3(4-5х)+2(3-6х)=-3,9
-12+15х+6-12х=-3,9
15х-12х=-3,9+12-6
3х=2,1
х=2,1/3
х=0,7
ответ 0,7
д)9(х-1)=х+15
9х-9=х+15
9х-х=15+9
8х=24
х=24/8
х=3
ответ 3
е)(11х+14)-(5х-8)=25
11х+14-5х+8=25
11х-5х=25-14-8
6х=3
х=3/6
х=0,5
ответ 0,5
ё)12-4(х-3)=39-9х
12-4х+12=39-9х
-4х+9х=39-12-12
5х=15
х=15/5
х=3
ответ 3
ж) 2(3х+5)-3(4х-1)=11,8
6х+10-12х+3=11,8
6х-12х=11,8-10-3
-6х=-1,2
-х=-1,2/6
-х=-0,2
х=0,2
ответ 0,2
129. 18 и 10; 4 и 45; 3 и 60; 2 и 90; 9 и 20; 5 и 36
130. 2 и 2; 1 и 4
Пошаговое объяснение:
129. 36 * 5 = 180 - произведение средних членов пропорции
180 = 180 * 1 180 : 36 = 5 : 1
180 = 18 * 10 18 : 36 = 5 : 10
180 = 4 * 45 4 : 36 = 5 : 45
180 = 3 * 60 3 : 36 = 5 : 60
180 = 2 * 90 2 : 36 = 5 : 90
180 = 9 * 20 9 : 36 = 5 : 20
180 = 5 * 36 5 : 36 = 5 : 36
130. 1,6 * 2,5 = 4 - произведение средних членов пропорции
4 = 2 * 2 1,6 : 2 = 2 : 2,5
4 = 1 * 4 1,6 : 1 = 4 : 2,5
4 = 4 * 1 1,6 : 4 = 1 : 2,5